Progress in the Study of Chinese and Western Medicine Treatment of Chronic Constipation in the Elderly - Duo, Deng; Li, Liu (Journal of Contemporary Medical Practice, 2025)
Chronic constipation is a common geriatric syndrome, which not only affects the quality of life, but also induces and aggravates cardiovascular and cerebrovascular diseases and intestinal diseases; it is a common clinical disease and a difficult clinical treatment. About 15% to 20% of the elderly aged 60 and above suffer from chronic constipation. With the further development of population aging, the treatment of chronic constipation in the elderly is becoming more and more important, and this paper provides a review of Western medicine treatment, Chinese medicine treatment and the combination of Chinese and Western medicine in the treatment of chronic constipation in the elderly, in order to provide reference for the future clinical treatment and scientific research.